Application of Student-Centered Learning in Improving Teaching English as a Foreign Language Students' 21st-Century Skills Performance - Hadiyanto Hadiyanto (MDPI AG, 2024)
A student-centered learning (SCL) method has been applied to improve Teaching English as a Foreign Language (TEFL) students' 21st-century skills at the English department of a university. Therefore, this study aimed to investigate the effect of SCL application on TEFL students' 21st-century skills performance. To achieve this objective, a total of 220 questionnaires were distributed to TEFL students, and ten course designs were obtained from the department. Content analysis on course designs showed that hard skills were more prioritized than soft skills, while character slightly ebbed in learning design. Furthermore, SCL application through Group, Independent, and Online learning methods significantly increased TEFL students' 21st-century skills. Hard and soft skills were most and slightly associated with cumulative grade point average (CGPA), respectively. These results showed that SCL should be properly applied to deliver course content and improve 21st-century skills performance.